Molecular sieve based photoelectric positive electrode, preparation method thereof and photo-assisted near-neutral zinc air battery
By carbonizing the Ti-rich titanium silicon molecular sieve precursor and ruthenium loading, a molecular sieve-based photoelectric catalyst was prepared, which solved the problem of insufficient catalytic activity and conductivity of neutral zinc-air batteries, and significantly improved the charge and discharge efficiency and energy density of the battery.
Patent Information
- Application Number
- CN202510333525.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-20
- Publication Date
- 2025-06-13
- Estimated Expiration
- 2045-03-20
AI Technical Summary
Neutral zinc-air batteries have high charge and discharge overpotential due to the low ionic conductivity of neutral electrolyte and insufficient catalytic activity of air positive electrode, which affects the energy density and service life of the battery.
By carbonizing the Ti-rich titanium silicon molecular sieve precursor and supporting the ruthenium element, a molecular sieve-based photoelectrometacatalyst was prepared, which significantly improved the electron conduction ability and catalytic activity, and overcomeded the problems of conductivity and contact resistance of titanium silicon molecular sieve.
While maintaining the long life and low corrosion advantages of neutral zinc-air batteries, the charging and discharging efficiency, rate performance and output power of the battery are significantly improved, and the charge and discharge overpotential is reduced.
Smart Images

Figure CN120149430A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electrochemistry, and particularly to a molecular sieve-based optoelectronic positive electrode, a preparation method thereof, and a photo-assisted near-neutral zinc-air battery. Background Art
[0002] With the rapid development of the global economy and the continuous improvement of people's requirements for the quality of life, the energy demand continues to grow. As a new type of green energy technology, zinc-air batteries have attracted extensive attention due to their high theoretical energy density (1360 Wh / kg), low cost, and environmental friendliness.
[0003] At present, alkaline zinc-air batteries (using 6 mol / L KOH as the electrolyte) have been applied in many fields, but there are problems such as electrolyte carbonation, carbon corrosion of the air positive electrode, self-discharge of the zinc negative electrode, and surface passivation, which seriously affect the service life and long-term power supply ability of the battery. In contrast, neutral zinc-air batteries exhibit a longer service life and lower corrosiveness, can effectively avoid various side reactions in the electrolyte of traditional alkaline zinc-air batteries, reduce the self-discharge process of the battery, improve the utilization efficiency of the zinc negative electrode, and thus enhance the energy density and service life of the battery, and have become a research hotspot in the current field. However, due to the relatively low ionization degree of neutral salts in aqueous solutions, the ionic conductivity of neutral electrolytes is low, resulting in the catalytic activity of the air positive electrode in the oxygen reduction reaction and oxygen evolution reaction not being comparable to that under alkaline conditions, and thus causing a relatively large charge-discharge overpotential in neutral zinc-air batteries.
[0004] Zeolite molecular sieve materials have many advantages, and there have been studies attempting to use the confinement effect of molecular sieves to design battery positive electrodes. However, most molecular sieves themselves have poor electrical conductivity, which becomes a limiting factor during the charge-discharge cycle of the battery, hinders the effective transmission of electrons, leads to an increase in battery polarization, a decrease in charge-discharge efficiency, and affects the rate performance and output power of the battery. In particular, the contact between the molecular sieve particles and the current collector is not tight and sufficient, resulting in a large contact resistance, which further hinders electron conduction, causing significant energy loss in neutral zinc-air batteries under high-current charge-discharge conditions. Summary of the Invention
[0005] Aiming at the deficiencies of the existing technology, the present invention provides a molecular sieve-based optoelectronic cathode, a preparation method thereof, and a photo-assisted near-neutral zinc-air battery. The present invention uses a Ti-rich titanium silicate molecular sieve precursor as a raw material, and carbonizes the Ti-rich titanium silicate molecular sieve precursor to obtain a carbonized Ti-rich titanium silicate molecular sieve; subsequently, the carbonized Ti-rich titanium silicate molecular sieve is impregnated in a ruthenium-containing element solution, and after drying, it is heat-treated in an atmosphere with a reducing gas to obtain a molecular sieve-based optoelectronic catalyst. By carbonizing the Ti-rich titanium silicate molecular sieve precursor and loading ruthenium elements, the present invention significantly improves the electron conduction ability of the molecular sieve-based optoelectronic catalyst, not only solves the problem of poor conductivity of the titanium silicate molecular sieve itself, but also overcomes the problem of large contact resistance caused by poor contact between the titanium silicate molecular sieve and the current collector, thereby realizing the significant improvement of the charge and discharge efficiency, rate performance, and output power of the battery while maintaining the advantages of long life and low corrosion of the neutral zinc-air battery.
[0006] To achieve the above object, the technical solution adopted by the present invention is as follows:
[0007] The first object of the present invention is to provide a preparation method of a molecular sieve-based optoelectronic catalyst, which includes the following steps:
[0008] S1. Mix a titanium source, a silicon source, and an organic template agent. The organic template agent is composed of a structure-directing agent and cetyltrimethylammonium bromide, and perform a hydrothermal reaction. After centrifugation, a Ti-rich titanium silicate molecular sieve precursor is obtained.
[0009] Among them, cetyltrimethylammonium bromide, as a surfactant, can interact with the titanium source through its long-chain alkyl group, promoting the uniform dispersion of the titanium source in the framework of the Ti-rich titanium silicate molecular sieve precursor; at the same time, it avoids the aggregation of the titanium source to form non-framework titanium, such as TiO 2 , thereby improving the effective utilization rate of titanium and enhancing the catalytic activity; compared with other more expensive organic template agents, cetyltrimethylammonium bromide shows good structure-directing effects under different pH values, temperatures, and synthesis conditions, with low price and wide applicability.
[0010] S2. In an inert atmosphere, carbonize the Ti-rich titanium silicate molecular sieve precursor. During the carbonization process, a part of the organic template agent in the Ti-rich titanium silicate molecular sieve is pyrolyzed into small molecule gases and removed, and the remaining part is pyrolyzed into carbonaceous residues and further carbonized, converting into intracrystalline carbon deposits to obtain a carbonized Ti-rich titanium silicate molecular sieve.
[0011] S3. Immerse the carbonized Ti-rich titanium silicate molecular sieve in a ruthenium-containing solution. During the immersion process, ruthenium ions in the ruthenium-containing solution are uniformly dispersed in the pores of the carbonized Ti-rich titanium silicate molecular sieve under the electrostatic adsorption of surface hydroxyl groups and the pore size confinement effect of the carbonized Ti-rich titanium silicate molecular sieve. After drying, a precursor is obtained. The pore size of the carbonized Ti-rich titanium silicate molecular sieve is about 0.7 nm, which is close to 3+ the kinetic diameter of Ru 3+ about 0.6 nm. Ru
[0012] ions can only diffuse into the interior of the carbonized Ti-rich titanium silicate molecular sieve through the pore openings. Large-particle-size particles or aggregated precursors are physically blocked outside, avoiding disordered surface accumulation. 3+ S4. In an atmosphere with a reducing gas, perform high-temperature treatment on the precursor. During the high-temperature treatment process, the adsorbed Ru
[0013] on the precursor is reduced to ruthenium nanoparticles and uniformly dispersed in the pores of the carbonized Ti-rich titanium silicate molecular sieve to obtain a molecular sieve-based photocatalyst.
[0014] Preferably, the molar ratio of the titanium source, silicon source, structure-directing agent, and cetyltrimethylammonium bromide is 1:25 - 50:63:0.3. Among them, the titanium source is a key element for the carbonized Ti-rich titanium silicate molecular sieve to play a catalytic role, and its content needs to provide sufficient active sites. If the titanium source is excessive, that is, the molar ratio of the titanium source to the silicon source is too high, it is easy to cause the formation of non-framework titanium. These non-framework titaniums not only cannot effectively participate in the catalytic reaction, but also block the pores of the carbonized Ti-rich titanium silicate molecular sieve, affecting the diffusion of ruthenium nanoparticles, and thus reducing the catalytic performance of the molecular sieve-based photocatalyst.
[0015] Preferably, the conditions for carbonization treatment are: calcination at 400 °C - 800 °C for 3 h - 6 h. Among them, if the calcination time is too long, the internal pores of the carbonized Ti-rich titanium silicate molecular sieve will collapse. 2 Preferably, the conditions for high-temperature treatment are: holding at 200 °C - 400 °C for 2 h - 4 h. Among them, if the holding time is too long, the ruthenium nanoparticles will agglomerate. When the temperature is higher than 400 °C, the diffusion rate of ruthenium atoms at high temperature increases significantly, and the pore size confinement effect of the carbonized Ti-rich titanium silicate molecular sieve is broken through, and the ruthenium nanoparticles undergo Ostwald ripening, resulting in an increase in their particle size and a decrease in dispersibility. When the temperature is low, the 3+ reduction ability is insufficient, and Ru 0 is only partially reduced and not completely converted into metallic Ru
[0016] which leads to a decrease in the performance of the molecular sieve-based photocatalyst.
[0017] Preferably, the atmosphere with reducing gas is selected from the mixed atmosphere of Ar gas and H 2 .
[0018] Preferably, in the mixed atmosphere of Ar gas and H 2 , the volume fraction of H 2 in the mixed atmosphere is 3% - 10%.
[0019] Preferably, the concentration of Ru 3+ in the ruthenium element-containing solution is 0.1 mol / L - 0.2 mol / L; this concentration range ensures the efficient anchoring and uniform distribution of ruthenium nanoparticles, thereby maximizing the catalytic activity and stability of the molecular sieve-based photocatalyst and avoiding the risk of low efficiency or failure. Among them, when the concentration is lower than 0.1 mol / L, the adsorption amount of ruthenium nanoparticles in the precursor is small, and the density of active sites is low, which cannot effectively improve the catalytic activity of the molecular sieve-based photocatalyst; when the concentration is higher than 0.2 mol / L, Ru 3+ rapidly adsorbs on the surface of carbonized Ti-rich titanium silicate molecular sieve and forms an overly thick liquid film. During the high-temperature treatment and drying process, the shrinkage stress causes the ruthenium nanoparticles to aggregate, and the pore structure of the Ti-rich titanium silicate molecular sieve is easily blocked, affecting the mass transfer efficiency.
[0020] Preferably, the ruthenium element-containing solution is selected from ruthenium trichloride solution, ruthenium nitrate solution or ruthenium acetylacetonate solution; among them, ruthenium salts with smaller particle sizes are preferably selected. If the radius of the ruthenium salt is too large, the internal pores of the carbonized Ti-rich titanium silicate molecular sieve cannot adsorb. During the high-temperature treatment process, the overly large ruthenium salt particles are prone to agglomeration, resulting in uneven distribution of ruthenium nanoparticles on the carbonized Ti-rich titanium silicate molecular sieve; this uneven distribution will reduce the effective exposure rate of ruthenium active sites and significantly reduce the utilization rate of the molecular sieve-based photocatalyst and ruthenium elements.
[0021] Preferably, the structure-directing agent is selected from tetrapropylammonium hydroxide, tetraethylammonium hydroxide or cetyltrimethylammonium bromide; among them, the molecular size and shape of tetrapropylammonium hydroxide molecules, as well as their appropriate alkalinity and good thermal stability, make the preparation process more stable and controllable.
[0022] Preferably, the silicon source is selected from tetraethyl orthosilicate, silica sol or water glass.
[0023] Preferably, the titanium source is selected from tetrabutyl titanate, titanium tetrachloride or titanium sulfate.
[0024] The second object of the present invention is to provide a molecular sieve-based photocatalyst prepared by the above preparation method.
[0025] Preferably, the molecular sieve-based photocatalyst has a regular and uniform polyhedron structure, and its internal pores are regular and orderly.
[0026] The third object of the present invention is to provide a molecular sieve-based photoanode, which is made of the above-mentioned molecular sieve-based photocatalyst, binder, conductive agent and current collector.
[0027] The fourth object of the present invention is to provide a method for preparing a molecular sieve-based photoanode, comprising the following steps: mixing the molecular sieve-based photocatalyst, conductive agent and binder, and coating the mixture on a current collector, followed by drying to obtain the molecular sieve-based photoanode.
[0028] Preferably, the conductive agent is selected from conductive carbon Super P, carbon nanotubes or Ketjen black; Super P is an amorphous carbon black with a particle size usually in the range of 40 nm to 50 nm. This relatively small and uniformly distributed particle size enables it to better mix with the molecular sieve-based photocatalyst. In contrast, carbon nanotubes usually have a large aspect ratio and are prone to entanglement and aggregation; although Ketjen black also has a relatively small particle size, its tendency to agglomerate is more obvious than that of Super P; while Super P can be evenly dispersed on the surface and in the gaps of molecular sieve particles to form a good conductive network.
[0029] Preferably, the binder is selected from Nafion solution, polyvinylidene fluoride or polytetrafluoroethylene; compared with PVDF and PTFE, Nafion solution has good ion conduction performance, can significantly accelerate the proton transfer process and effectively reduce the internal resistance; at the same time, Nafion solution also has excellent chemical stability and binding performance.
[0030] Preferably, the current collector is selected from carbon paper, carbon cloth or nickel foam.
[0031] The fifth object of the present invention is to provide a photo-assisted near-neutral zinc-air battery, which is composed of the above-mentioned molecular sieve-based photoanode, separator, cathode and electrolyte.
[0032] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0033] 1. The present invention provides a method for preparing a molecular sieve-based photocatalyst. In an inert atmosphere, a Ti-rich titanium silicate molecular sieve precursor is carbonized. During the carbonization process, part of the organic template agent in the Ti-rich titanium silicate molecular sieve thermally cracks into small molecule gases and is removed, and the remaining part thermally cracks into carbonaceous residues and is further carbonized to be converted into intracrystalline carbon deposits, obtaining a carbonized Ti-rich titanium silicate molecular sieve; the carbonized Ti-rich titanium silicate molecular sieve is impregnated in a ruthenium-containing element solution. During the impregnation process, Ru in the ruthenium-containing element solution 3+, under the electrostatic adsorption and pore size confinement of the surface hydroxyl groups of the carbonized Ti-rich titanium silicalite molecular sieve, it is uniformly dispersed in the pores of the carbonized Ti-rich titanium silicalite molecular sieve, and after drying, a precursor is obtained; in an atmosphere with a reducing gas, the precursor is subjected to high-temperature treatment. During the high-temperature treatment, the Ru adsorbed on the precursor 3+ is reduced to ruthenium nanoparticles and uniformly dispersed in the pores of the carbonized Ti-rich titanium silicalite molecular sieve to obtain a molecular sieve-based photocatalyst. By carbonizing the Ti-rich titanium silicalite molecular sieve precursor and loading ruthenium elements, the present invention significantly improves the electron conduction ability of the molecular sieve-based photocatalyst, not only solving the problem of poor conductivity of the titanium silicalite molecular sieve itself, but also because the particle size of the molecular sieve-based photocatalyst of the present invention is relatively small, about 200 nm. The small size helps to reduce the packing voids between the molecular sieve-based photocatalyst particles, thereby increasing the contact point density with the current collector and overcoming the problem of large contact resistance caused by poor contact between the titanium silicalite molecular sieve raw powder and the current collector. Thus, while maintaining the advantages of long life and low corrosiveness of the near-neutral zinc-air battery, the charge-discharge efficiency, rate performance and output power of the battery are significantly improved.
[0034] 2. The selected Ti-rich titanium silicalite molecular sieve precursor of the present invention has light responsiveness and a high framework Ti content. By introducing the organic template cetyltrimethylammonium bromide to regulate the hydrolysis process of the reaction solution, it is helpful to obtain the Ti-rich titanium silicalite molecular sieve precursor. This structure can provide more photoactive centers, thereby accelerating the rate of the photocatalytic reaction. In addition, when the Ti-rich titanium silicalite molecular sieve precursor is carbonized, under the thermal drive, dehydration condensation reactions occur between adjacent Si-OH or Ti-OH groups in the framework of the Ti-rich titanium silicalite molecular sieve precursor to form Si-O-Si or Ti-O-Ti bonds, thereby realizing the reconstruction of the structure. This process not only helps to strengthen the framework structure of the Ti-rich titanium silicalite molecular sieve, improve its thermal stability and chemical stability, but also can effectively dredge the electron conduction path, thereby significantly improving the conductivity of the Ti-rich titanium silicalite molecular sieve precursor. At the same time, the carbonization treatment also increases the number of active sites of the carbonized Ti-rich titanium silicalite molecular sieve. The ability of these active sites to capture and respond to light becomes more sensitive, laying a foundation for the improvement of battery performance.
[0035] 3. The molecular sieve-based photocatalyst of the present invention has adjustable pore sizes and excellent performance in catalyzing the oxygen reduction reaction and oxygen evolution reaction. This is because the present invention uses a titanium-rich and highly conductive titanium silicon molecular sieve with carbonized Ti as the substrate material. By the impregnation method and utilizing the ordered pore structure of the carbonized Ti titanium silicon molecular sieve to impose a confinement effect on ruthenium nanoparticles, it is ensured that the ruthenium nanoparticles can be uniformly loaded into the internal structure of the carbonized Ti titanium silicon molecular sieve, effectively avoiding the agglomeration tendency of the ruthenium nanoparticles. In addition, the formed small-sized ruthenium nanoparticles not only greatly promote the transfer process of photo-generated electrons in the carbonized Ti titanium silicon molecular sieve to ruthenium, significantly shortening the electron transport distance, but also accelerate the oxygen reduction and oxygen evolution kinetic processes under photo-assisted conditions, achieving efficient photocatalytic performance.
[0036] 4. The molecular sieve-based photocatalyst of the present invention has a high specific surface area, high stability, and a rich and ordered pore structure, such as countless tiny "high-speed channels", which significantly accelerates the diffusion of reactant molecules, shortens the time for reactants to reach the active sites, and thus greatly improves the oxygen reduction reaction rate.
[0037] The molecular sieve-based photocatalyst of the present invention is made into a molecular sieve-based photoanode. When the molecular sieve-based photoanode is irradiated with light, the carbonized Ti titanium silicon molecular sieve creates an ideal "working environment" for ruthenium nanoparticles by virtue of its unique pore structure and conductivity. It can not only accelerate electron transfer but also accurately provide a transfer path for photo-generated electrons, effectively reducing the carrier recombination efficiency, enabling rapid photoelectric conversion inside the battery, and greatly improving the charge and discharge performance of the battery.
[0038] 5. Combining the molecular sieve-based photoanode prepared by the present invention with a photo-assisted technology in a near-neutral zinc-air battery can not only improve the slow mass transfer process in the electrolyte, significantly enhancing the power density and energy utilization efficiency of the battery, but also exhibit a low charge and discharge overpotential, thereby enhancing the charge and discharge efficiency of the battery, and having excellent round-trip efficiency and cycle stability, providing strong support for obtaining a stable and rechargeable near-neutral zinc-air battery.
[0039] In the photo-assisted near-neutral zinc-air battery, the molecular sieve-based photoanode of the present invention exhibits extremely rapid photo-generated electron transfer kinetics and a high photo-generated carrier separation efficiency. These two work together to effectively enhance the oxygen reduction reaction and oxygen evolution reaction kinetic processes at the molecular sieve-based photoanode, significantly reducing the polarization overpotential during the charge and discharge process of the photo-assisted near-neutral zinc-air battery, and thus significantly improving the power density of the photo-assisted near-neutral zinc-air battery. Among them, during the catalytic oxygen reduction reaction process, its ruthenium sites can accurately and efficiently adsorb oxygen molecules, accelerating the conversion of oxygen to products; while during the catalytic oxygen evolution reaction process, it can promote the decomposition of products into oxygen, making the reaction faster and more efficient. Brief Description of the Drawings
[0040] Figure 1 Scanning electron microscope image of the Ti-rich titanium silicalite molecular sieve prepared in Comparative Example 1.
[0041] Figure 2 Scanning electron microscope images of the carbonized Ti-rich titanium silicalite molecular sieve prepared in Examples 1 to 3, where a is Example 1, b is Example 2, and c is Example 3.
[0042] Figure 3 Steady-state fluorescence spectra of the carbonized Ti-rich titanium silicalite molecular sieve prepared in Examples 1 to 3 and the Ti-rich titanium silicalite molecular sieve prepared in Comparative Example 1.
[0043] Figure 4 Charge-discharge plateau curve graphs of the near-neutral zinc-air battery assembled with the molecular sieve-based optoelectronic cathode prepared from TS@C-800 of Application Example 3 under illumination and non-illumination.
[0044] Figure 5 Transmission electron microscope image of the molecular sieve-based optoelectronic catalyst prepared in Example 3.
[0045] Figure 6 Current-time light response curve graphs of TS@C-800 and Ru@TS@C-800 prepared in Example 3 to ultraviolet light.
[0046] Figure 7 Charge-discharge plateau curve graphs of the light-assisted near-neutral zinc-air battery assembled with the molecular sieve-based optoelectronic cathode prepared from TS@C-800 and Ru@TS@C-800 of Application Example 3. Detailed Description of the Invention
[0047] Next, the technical solutions of the present invention will be clearly and completely described in conjunction with the data in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative efforts fall within the scope of protection of the present invention.
[0048] It should be noted that the professional terms used in the present invention are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specifically stated, all kinds of raw materials, reagents, instruments, and equipment used in the following embodiments of the present invention can be obtained through market purchase or prepared by existing methods.
[0049] In the prior art, although neutral zinc-air batteries have shown significant advantages in improving battery life and reducing corrosion, their performance is still limited by the low ionic conductivity of the neutral electrolyte and the insufficient catalytic activity of the air cathode. To address this issue, researchers have explored various methods to enhance the catalytic efficiency and electron conduction ability of the cathode, including the use of high-performance catalysts and the improvement of electrode structures. However, these methods often face challenges such as high catalyst costs, complex preparation processes, or poor compatibility between the catalyst and electrode materials. In particular, for zeolite-based materials, although their unique pore structure and confinement effect provide favorable conditions for the dispersion of catalysts, their low conductivity and poor contact with current collectors limit their practical application in neutral zinc-air batteries.
[0050] The present invention addresses the problems existing in the above prior art and provides a method for preparing a zeolite-based photo-electrocatalyst, which includes the following steps: mixing a titanium source, a silicon source, and an organic template agent, where the organic template agent consists of a structure-directing agent and cetyltrimethylammonium bromide, performing a hydrothermal reaction, and obtaining a Ti-rich titanium silicate molecular sieve precursor through centrifugation; in an inert atmosphere, carbonizing the Ti-rich titanium silicate molecular sieve precursor. During the carbonization process, part of the organic template agent in the Ti-rich titanium silicate molecular sieve thermally decomposes into small-molecule gases and is removed, and the other part thermally decomposes into carbonaceous residues and is further carbonized, converting into intracrystalline carbon deposits to obtain a carbonized Ti-rich titanium silicate molecular sieve; impregnating the carbonized Ti-rich titanium silicate molecular sieve in a ruthenium-containing solution. During the impregnation process, Ru in the ruthenium-containing solution 3+ is uniformly dispersed in the pores of the carbonized Ti-rich titanium silicate molecular sieve under the electrostatic adsorption of surface hydroxyl groups and the pore size confinement effect of the carbonized Ti-rich titanium silicate molecular sieve, and after drying, a precursor is obtained; in an atmosphere with a reducing gas, performing a high-temperature treatment on the precursor. During the high-temperature treatment, the adsorbed Ru on the precursor 3+ is reduced to ruthenium nanoparticles and is uniformly dispersed in the pores of the carbonized Ti-rich titanium silicate molecular sieve to obtain a zeolite-based photo-electrocatalyst.
[0051] By carbonizing the Ti-rich titanium silicate molecular sieve precursor and loading ruthenium elements, the present invention significantly improves the electron conduction ability of the zeolite-based photo-electrocatalyst, not only solving the problem of poor conductivity of the titanium silicate molecular sieve itself, but also overcoming the problem of large contact resistance caused by poor contact between the titanium silicate molecular sieve and the current collector. Thus, while maintaining the advantages of long life and low corrosion of neutral zinc-air batteries, the charge-discharge efficiency, rate performance, and output power of the battery are significantly improved.
[0052] To enable those skilled in the art to more clearly understand the technical solution of the present invention, the following will detail the technical solution of the present invention in combination with specific embodiments.
[0053] Example 1
[0054] A preparation method of a molecular sieve-based photocatalyst includes the following steps:
[0055] S1. Take 50 mL of isopropanol and place it in a beaker. Add 1.75 mL of tetrabutyl titanate and 20 mL of tetrapropylammonium hydroxide, and stir at room temperature for 1 h to obtain reaction solution I; take another 44 mL of tetrapropylammonium hydroxide in a beaker, add 0.58 g of cetyltrimethylammonium bromide, and then dropwise add 50 mL of tetraethyl orthosilicate, and stir vigorously for 1 h to obtain reaction solution II.
[0056] S2. Slowly drop reaction solution I into reaction solution II, stir vigorously at room temperature for 2 h, then carry out alcohol removal treatment at 80 °C for 30 min, and supplement with deionized water during this period; then transfer it into a polytetrafluoroethylene reaction kettle, carry out hydrothermal reaction at 170 °C for 48 h, cool to room temperature, and wash the product three times with water and ethanol respectively; then dry the product at 100 °C for 12 h to obtain a Ti-rich titanium silicate molecular sieve precursor.
[0057] S3. Place the Ti-rich titanium silicate molecular sieve precursor in a tube furnace, heat it to 400 °C at a rate of 3 °C / min under a nitrogen atmosphere, calcine for 3 h, and then cool naturally to obtain a carbonized Ti-rich titanium silicate molecular sieve, denoted as TS@C-400.
[0058] S4. Dissolve 60 mg of ruthenium trichloride in 2 mL of deionized water, then add 400 mg of TS@C-400, stir for 12 h, dry at 80 °C, and then place it in a tube furnace and linearly heat it to 400 °C under a mixed atmosphere of Ar and H 2 Keep it at this temperature for 2 h and then cool naturally to obtain a molecular sieve-based photocatalyst, denoted as Ru@TS@C-400.
[0059] Example 2
[0060] A preparation method of a molecular sieve-based photocatalyst is the same as the preparation steps of Example 1, except that the calcination temperature in S3 is replaced by 600 °C, and it includes the following steps:
[0061] S1. Take 50 mL of isopropanol and place it in a beaker. Add 1.75 mL of tetrabutyl titanate and 20 mL of tetrapropylammonium hydroxide, and stir at room temperature for 1 h to obtain reaction solution I; take another 44 mL of tetrapropylammonium hydroxide in a beaker, add 0.58 g of cetyltrimethylammonium bromide, and then dropwise add 50 mL of tetraethyl orthosilicate, and stir vigorously for 1 h to obtain reaction solution II.
[0062] S2. Slowly drop the reaction solution I into the reaction solution II, stir vigorously at room temperature for 2 h, then carry out alcohol removal treatment at 80 °C for 30 min, and supplement with deionized water during this period; then transfer it into a polytetrafluoroethylene reaction kettle, carry out hydrothermal reaction at 170 °C for 48 h, wash the product three times with water and ethanol respectively after cooling to room temperature; then dry the product at 100 °C for 12 h to obtain a Ti-rich titanium silicalite molecular sieve precursor.
[0063] S3. Place the Ti-rich titanium silicalite molecular sieve precursor in a tubular furnace, heat it to 600 °C at a rate of 3 °C / min under a nitrogen atmosphere, calcine for 3 h, and then cool naturally to obtain a carbonized Ti-rich titanium silicalite molecular sieve, denoted as TS@C-600.
[0064] S4. Dissolve 60 mg of ruthenium trichloride in 2 mL of deionized water, then add 400 mg of TS@C-600, stir for 12 h, dry at 80 °C, and then place it in a tubular furnace and linearly heat it to 400 °C under a mixed atmosphere of Ar and H 2 , keep it at this temperature for 2 h, and then cool naturally to obtain a molecular sieve-based photocatalyst, denoted as Ru@TS@C-600.
[0065] Example 3
[0066] A preparation method of a molecular sieve-based photocatalyst is the same as the preparation steps of Example 1, except that the calcination temperature in S3 is replaced from 400 °C to 800 °C, and it includes the following steps:
[0067] S1. Take 50 mL of isopropanol and place it in a beaker, add 1.75 mL of tetrabutyl titanate and 20 mL of tetrapropylammonium hydroxide, and stir at room temperature for 1 h to obtain reaction solution I; take another 44 mL of tetrapropylammonium hydroxide in a beaker, add 0.58 g of cetyltrimethylammonium bromide, and then dropwise add 50 mL of tetraethyl orthosilicate and stir vigorously for 1 h to obtain reaction solution II.
[0068] S2. Slowly drop the reaction solution I into the reaction solution II, stir vigorously at room temperature for 2 h, then carry out alcohol removal treatment at 80 °C for 30 min, and supplement with deionized water during this period; then transfer it into a polytetrafluoroethylene reaction kettle, carry out hydrothermal reaction at 170 °C for 48 h, wash the product three times with water and ethanol respectively after cooling to room temperature; then dry the product at 100 °C for 12 h to obtain a Ti-rich titanium silicalite molecular sieve precursor.
[0069] S3. Place the Ti-rich titanium silicalite molecular sieve precursor in a tubular furnace, heat it to 800 °C at a rate of 3 °C / min under a nitrogen atmosphere, calcine for 3 h, and then cool naturally to obtain a carbonized Ti-rich titanium silicalite molecular sieve, denoted as TS@C-800.
[0070] S4. Dissolve 60 mg of ruthenium trichloride in 2 mL of deionized water, then add 400 mg of TS@C-800, stir for 12 h and dry at 80 °C, then place it in a tubular furnace and linearly heat it to 400 °C under a mixed atmosphere of Ar and H 2 and keep it at this temperature for 2 h, and then cool it naturally to obtain a molecular sieve-based photocatalyst, denoted as Ru@TS@C-800.
[0071] Example 4
[0072] A method for preparing a molecular sieve-based photocatalyst, comprising the following steps:
[0073] S1. Take 50 mL of isopropanol and place it in a beaker, add 1.75 mL of tetrabutyl titanate and 20 mL of tetrapropylammonium hydroxide, and stir at room temperature for 1 h to obtain reaction solution I; take another 44 mL of tetrapropylammonium hydroxide in a beaker, add 0.58 g of cetyltrimethylammonium bromide, and then dropwise add 25 mL of tetraethyl orthosilicate and stir vigorously for 1 h to obtain reaction solution II.
[0074] S2. Slowly drop reaction solution I into reaction solution II, stir vigorously at room temperature for 2 h and then carry out alcohol removal treatment at 80 °C for 30 min, and supplement with deionized water during this period; then transfer it into a polytetrafluoroethylene reaction kettle and carry out hydrothermal reaction at 170 °C for 48 h, cool to room temperature and wash the product three times with water and ethanol respectively; then dry the product at 100 °C for 12 h to obtain a Ti-rich titanium silicate molecular sieve precursor.
[0075] S3. Place the Ti-rich titanium silicate molecular sieve precursor in a tubular furnace, heat it to 800 °C at a rate of 3 °C / min under a nitrogen atmosphere, calcine for 3 h and then cool it naturally to obtain a carbonized Ti-rich titanium silicate molecular sieve, denoted as TS@C-800.
[0076] S4. Dissolve 60 mg of ruthenium trichloride in 2 mL of deionized water, then add 400 mg of TS@C-800, stir for 12 h and dry at 80 °C, then place it in a tubular furnace and linearly heat it to 200 °C under a mixed atmosphere of Ar and H 2 and keep it at this temperature for 4 h, and then cool it naturally to obtain a molecular sieve-based photocatalyst.
[0077] Comparative Example 1
[0078] A method for preparing a Ti-rich titanium silicate molecular sieve, comprising the following steps:
[0079] S1. Place 50 mL of isopropanol in a beaker, add 1.75 mL of tetrabutyl titanate and 20 mL of tetrapropylammonium hydroxide, and stir for 1 h at room temperature to obtain reaction solution I; separately, take 44 mL of tetrapropylammonium hydroxide in a beaker, add 0.58 g of cetyltrimethylammonium bromide, and then gradually add 50 mL of tetraethyl orthosilicate dropwise while stirring vigorously for 1 h to obtain reaction solution II.
[0080] S2. Slowly drop reaction solution I into reaction solution II, stir vigorously at room temperature for 2 h, then carry out alcohol removal treatment at 80 °C for 30 min, and supplement with deionized water during this period; then transfer it into a polytetrafluoroethylene reaction kettle, carry out hydrothermal reaction at 170 °C for 48 h, wash the product three times with water and ethanol respectively after cooling to room temperature; then dry the product at 100 °C for 12 h to obtain a Ti-rich titanium silicate molecular sieve precursor.
[0081] S3. Heat the Ti-rich titanium silicate molecular sieve precursor in a muffle furnace from room temperature to 550 °C at a rate of 3 °C / min in an air atmosphere, keep it at this temperature for 6 h, and then cool it naturally to obtain a Ti-rich titanium silicate molecular sieve, denoted as TS.
[0082] Observation Figure 1 It is concluded that the Ti-rich titanium silicate molecular sieve prepared in Example 3 of the present invention has a regular and uniform polyhedral structure. The regular polyhedral morphology can provide a larger specific surface area, increase the exposure of active sites, and is beneficial to the adsorption of reactants and the progress of photocatalytic reactions; while the polyhedral structure can enhance the scattering and absorption of light, improve the light energy utilization rate, and thus enhance the photocatalytic efficiency. Therefore, the Ti-rich titanium silicate molecular sieve with polyhedral morphology significantly improves the photocatalytic performance by optimizing light absorption, mass transfer, charge separation, and active site distribution.
[0083] Observation Figure 2 It is concluded that with the change of the calcination temperature, there are no significant differences in the morphology of the carbonized molecular sieve-based photocatalysts prepared in Examples 1 to 3, and they can still maintain the polyhedral structure characteristics of the original Ti-rich titanium silicate molecular sieve, and the sizes remain consistent, showing good uniformity.
[0084] It is concluded from Figure 3 that the fluorescence intensity of TS@C-800 is the lowest, indicating that it can effectively reduce the recombination efficiency of photogenerated carriers, is beneficial to the separation of photogenerated electrons and holes, and can achieve a better photocatalytic process.
[0085] The TS@C-800 and Ru@TS@C-800 of Example 3 of the present invention and the TS of Comparative Example 1 and conductive carbon SurperP were respectively dispersed in ethanol at a mass ratio of 7:3, and a small amount of 5wt% binder Nafion solution was added. After ultrasonic dispersion, they were uniformly coated on both sides of the hydrophobic carbon paper. After drying, molecular sieve-based optoelectronic anodes were obtained, denoted as TS@C-800-ZJ, Ru@TS@C-800-ZJ, and TS-ZJ respectively.
[0086] Next, using TS@C-800-ZJ, Ru@TS@C-800-ZJ, and TS-ZJ as anodes, they were applied to the assembly of a near-neutral zinc-air battery and studied:
[0087] Using TS@C-800-ZJ, Ru@TS@C-800-ZJ, and TS-ZJ as catalytic anodes respectively, a modular near-neutral zinc-air battery was assembled in the order of negative electrode plate, zinc negative electrode, aqueous separator, electrolyte chamber, catalytic anode, and nickel foam current collector. After adding 1mol / L zinc trifluoromethanesulfonate electrolyte and standing, a near-neutral zinc-air battery was obtained. After the open-circuit voltage was stable, an LED ultraviolet light source about 5 cm away from the molecular sieve-based optoelectronic anode was turned on. After 20 minutes of illumination, the battery performance test was started. Under the condition of a current density of 0.2 mA / cm 2 the performance of the charge-discharge platform was tested.
[0088] It is Figure 4 concluded that the photo-generated electrons and holes excited by the molecular sieve-based optoelectronic anode prepared with TS@C-800 of Example 3 under illumination can effectively accelerate the oxygen reduction reaction and oxygen evolution reaction processes, and obtain a lower charge-discharge overpotential.
[0089] It is Figure 5 concluded that due to the confinement effect of the pore structure of the carbonized Ti-rich titanium silicate molecular sieve, the growth of ruthenium nanoparticles is effectively restricted and kept stable, avoiding significant particle aggregation. The average particle size of these ruthenium nanoparticles is relatively small, about 2 nm to 3 nm, and shows good dispersion uniformity. This characteristic indicates that the photo-assisted battery can accelerate the electron transfer process at the anode, thereby improving the overall performance of the battery.
[0090] It is Figure 6 concluded that compared with TS@C-800, the photocurrent of Ru@TS@C is significantly enhanced, indicating that Ru, as an electron capturer, effectively captures photo-generated electrons, reduces the recombination probability of photo-generated carriers, enables it to extract more photo-generated electrons, and thus enhances the photo-response signal.
[0091] It is Figure 7It is concluded that, compared with TS@C-800-ZJ, Ru@TS@C-800-ZJ can further enhance the reaction kinetic process of the battery and effectively reduce the charge-discharge polarization potential of the photo-assisted near-neutral zinc-air battery. After Ru is loaded on TS@C-800, it provides additional active sites for the photocatalytic reaction process. These active sites can adsorb reactant molecules and promote the interaction between photo-generated carriers and reactants, thereby increasing the reaction rate and the intensity of light response, and effectively improving the round-trip efficiency of the near-neutral zinc-air battery.
[0092] The molecular sieve-based optoelectronic cathode of the present invention has light responsiveness. The unique pore structure of titanium silicate molecular sieve rich in Ti is used to accelerate the mass transfer process of reactant molecules and ions in the battery. At the same time, the nano-scale ruthenium nanoparticles are obtained by combining its pore confinement effect to construct a fast photo-generated electron transfer channel. During the oxygen reduction process, the ruthenium sites can accurately and efficiently adsorb oxygen molecules and accelerate the conversion of oxygen to products; while during the oxygen evolution process, it can also help the products to decompose and convert into oxygen, making the whole reaction process proceed more rapidly and efficiently. Thanks to the above advantages, Ru@TS@C-800-ZJ exhibits a lower charge-discharge overpotential in the near-neutral zinc-air battery, which not only improves the charge-discharge efficiency of the near-neutral zinc-air battery, but also enables a relatively stable and rechargeable near-neutral zinc-air battery, promising to open a new chapter in the development of near-neutral zinc-air batteries.
[0093] It should be noted that when the present invention involves a numerical range, it should be understood that any value between the two endpoints of each numerical range and any one of the two endpoints can be selected. Since the steps and methods adopted are the same as those in the embodiments, in order to prevent repetition, the present invention describes the preferred embodiments. Although the preferred embodiments of the present invention have been described, those skilled in the art can make additional changes and modifications to these embodiments once they know the basic creative concept. Therefore, the appended claims are intended to be construed as including the preferred embodiments and all changes and modifications falling within the scope of the present invention.
[0094] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalent technologies, the present invention also intends to include these modifications and variations.
Claims
1. A method for preparing a molecular sieve-based photoelectrocatalyst, characterized in that: The steps include: A titanium source, a silicon source and an organic template are mixed, wherein the organic template is composed of a structure directing agent and hexadecyltrimethylammonium bromide, and subjected to a hydrothermal reaction and a centrifugal treatment to obtain a Ti-rich titanium silicon molecular sieve precursor; In an inert atmosphere, a Ti-rich titanium silicon molecular sieve precursor is subjected to a carbonization treatment. During the carbonization treatment, a portion of the organic template in the Ti-rich titanium silicon molecular sieve precursor is thermally cracked into small molecular gases and removed, and another portion is thermally cracked into carbonaceous residues and further carbonized to be converted into carbon deposits in the pores, thereby obtaining a carbonized Ti-rich titanium silicon molecular sieve; The carburized Ti-rich titanium silicon molecular sieve is immersed in a ruthenium-containing solution. During the immersion process, the Ru in the ruthenium-containing solution 3+ Under the electrostatic adsorption effect of the hydroxyl groups on the surface of the carbonized Ti-rich titanium silicon molecular sieve and the effect of pore size confinement, the precursor is uniformly dispersed in the pores of the carbonized Ti-rich titanium silicon molecular sieve, and is dried to obtain a precursor; In an atmosphere with a reducing gas, the precursor is subjected to a high temperature treatment. During the high temperature treatment, the Ru adsorbed on the precursor 3+ It is reduced to ruthenium nanoparticles and evenly dispersed in the pores of the carbonized Ti-rich titanium silicon molecular sieve to obtain a molecular sieve-based photoelectric catalyst.
2. The method for preparing a molecular sieve-based photoelectrocatalyst according to claim 1, characterized in that: The molar ratio of the titanium source, the silicon source, the structure directing agent and hexadecyltrimethylammonium bromide is 1:25-50:63:0.
3.
3. The method for preparing a molecular sieve-based photoelectrocatalyst according to claim 1, characterized in that: The conditions of the carbonization treatment are: calcination at 400°C to 800°C for 3h to 6h.
4. The method for preparing a molecular sieve-based photoelectrocatalyst according to claim 1, characterized in that: The conditions for high temperature treatment are: keeping warm at 200℃~400℃ for 2h~4h.
5. The method for preparing a molecular sieve-based photoelectrocatalyst according to claim 1, characterized in that: The conditions of the hydrothermal reaction are: crystallization at 170°C for 16h to 48h.
6. The method for preparing a molecular sieve-based photoelectrocatalyst according to claim 1, characterized in that: Ru in ruthenium-containing solution 3+ The concentration is 0.1mol / L~0.2mol / L.
7. A molecular sieve-based photoelectrocatalyst prepared by the preparation method according to any one of claims 1 to 6, characterized in that: Molecular sieve-based photoelectrocatalysts present a regular and uniform polyhedral structure, and their internal pores are regular and orderly.
8. A molecular sieve-based photoelectric cathode, characterized in that: The molecular sieve-based photoelectric positive electrode is made of the molecular sieve-based photoelectric catalyst according to claim 7, a binder, a conductive agent and a current collector.
9. The method for preparing a molecular sieve-based photoelectric anode according to claim 8, characterized in that: The following steps are involved: The molecular sieve-based photoelectric catalyst, the conductive agent and the binder are mixed, coated on a current collector, and dried to obtain a molecular sieve-based photoelectric positive electrode.
10. A light-assisted near-neutral zinc-air battery, characterized in that: The light-assisted near-neutral zinc-air battery is composed of the molecular sieve-based photoelectric positive electrode as claimed in claim 9, a separator, a negative electrode and an electrolyte.
Citation Information
Patent Citations
Titanium-silicon (TS-1) molecular sieve catalyst, preparation method and application of titanium-silicon (TS-1) molecular sieve catalyst in olefin epoxidation reaction
CN110813373A
Preparation method and application of novel titanium silicalite molecular sieve
CN112604711A
Preparation method of carbon molecular sieve-cobalt monatomic catalyst for zinc air battery
CN114284512A
Non-alkaline zinc-air battery using porous carbon catalyst
CN118213548A
Monolithic catalyst containing titanium silicalite molecular sieve coating as well as preparation method and application of monolithic catalyst
CN119588412A